Voices of young women leaving care: 'I did not have anywhere to go…so I went with a man' - Petra Roberts (Scottish Journal of Residential Child Care)
Transitioning into adulthood can be difficult for many young people but transitioning from residential care comes with challenges to those who have grown up away from parents and family. This paper will present the voices of young women in Trinidad and Tobago and the challenges they faced transitioning from residential care. Their voices highlight the need to think in more gendered terms when contemplating effective strategies for facilitating transitions from out of home care.